2017
DOI: 10.3171/2016.5.peds13345
|View full text |Cite
|
Sign up to set email alerts
|

Possible toxicity following embolization of congenital giant vertex hemangioma: case report

Abstract: The authors describe the case of a 3-year-old boy with a giant congenital vertex hemangioma who underwent presurgical embolization with Onyx (ethylene-vinyl alcohol copolymer dissolved in dimethyl sulfoxide) and Glubran (N-butyl-2-cyanoacrylate). This vascular tumor had no intracranial vascular communication as assessed by pre-embolization MRI and catheter angiography. All embolizations were performed by direct percutaneous injection. One week following the last embolization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…We speculate that the embolic agent may induce the formation of microthrombi in the spinal cord, thereby increasing the risk of LD in EVT patients. Embolic agents have been shown to have toxic effects on nervous tissue ( 24 26 ). Therefore, it is speculated that the toxic effects of embolic agents on the delicate spinal cord may be another important reason why EVT patients are more susceptible to LD.…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the embolic agent may induce the formation of microthrombi in the spinal cord, thereby increasing the risk of LD in EVT patients. Embolic agents have been shown to have toxic effects on nervous tissue ( 24 26 ). Therefore, it is speculated that the toxic effects of embolic agents on the delicate spinal cord may be another important reason why EVT patients are more susceptible to LD.…”
Section: Discussionmentioning
confidence: 99%
“…Propranolol, vincristine and corticosteroids have been utilized with limited effectiveness 29 . Embolization is usually utilized as an additional bleeding control method 31,32 . Surgical excision is the only treatment method that has been demonstrated to be de nitive 33,34 .…”
Section: Discussionmentioning
confidence: 99%
“…Other scholars found that glue can cause neuronal necrosis, nerve fiber rupture and demyelination, and lead to T lymphocytes, mast cells and macrophages infiltration. It suggests that the application of medical glue to nervous tissue or other sensitive tissues must be carefully selected [17, 18]. In our early study, most patients did not have adverse reactions although medical glue was not completely removed from deep orbital lesions.…”
Section: Discussionmentioning
confidence: 99%